Stability Indicating Analytical Method Development and Validation of Efavirenz Quantification by High Performance Liquid Chromatographic Technique - R. Kumar; M. Sharma; G. R. Verma (E-Journal of Chemistry)
A stability-indicating high performance liquid chromatography (HPLC) method is developed for the quantification of efavirenz drug substance. Selected mobile phase is a combination of 50 volume of acetonitrile and 50 volume of 0.86% w/v solution of ammonium dihydrogen phosphate, pH adjusted to 3.0 with orthophosphoric acid. Optimized column is a stainless steel column packed with base deactivated octa decylsilyl silica gel and at 252 nm wavelength. Linearity of the method is found 40 μg/mL to 160 μg/mL with regression coefficient of 0.9995. The method is validated according to ICH guidelines.